Taller regional de mejoramiento de frijol. Trabajos en campo - Orozco S., S.H. (Programa Cooperativo Regional de Frijol para Centroamérica, México y el Caribe (PROFRIJOL), 1989)
The different activities involved in the daily management of a breeding program, as implemented in the Regional Bean Workshop carried out in Jutiapa, Guatemala, are indicated. Observations recorded in a bean lot subjected to BGMV stress are also given; on a 1 to 9 damage scale, the susceptible control BAT 155 scored 9 and the tolerant control DOR 364, 3-4. Chemical measures to control Bemisia tabaci using carbosulfan, carbofuran, acephate, and methamidophos are indicated. (CIAT)